Meaningful Learning in Cosmology teaching from a Neuroscience perspective (Research, Society and Development, 2022)
In this work, an investigation was carried out on the interlocution between Neuroscience and Meaningful Learning, for the teaching of Cosmology. In this perspective, a question was asked: from the interface between Neuroscience and Meaningful Learning, what contributions can be evidenced for the teaching of Cosmology? The research, of basic nature and qualitative approach, adopted as parameter national official documents and the results of previous research described in articles, dissertations and theses, in the period from 1976 to 2021. The results reveal that the understanding of architecture and neural functioning will be favorable for the training of teachers, allowing them to adopt methods and practices that promote meaningful learning in Cosmology. However, the approximation between these areas should occur with caution, in order to avoid an immediate, simplistic and prescriptive appropriation of neurobiological concepts.